Julián Ríos and literary contemporaneity: cosmopolitanisms of a Spain out of joints - Hidalgo, Max (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Julián Ríos’s work has an eccentric place – even a non-place – in Spanish historiography and literary criticism. That is due not only to his own work but rather to the legacy of its critical discourses. It is worth thinking about Ríos’s trajectory and writings from a scope that bypasses the Spanish peninsular context, a space that includes authors like Octavio Paz, Haroldo de Campos, Guillermo Cabrera Infante or Emir Rodríguez Monegal. This new perspective would help revise his literary project and understand the specificity of his plural literary proposal, which had in the “Larva operation” a remarkable moment. The article questions the limits of Spanish criticism and literary historiography by reviewing Ríos’s editorial work in the “Espiral” series of Fundamentos and locating his literary project in relation to a constellation of authors who present themselves as cosmopolitan. In doing so, the article also celebrates the publication of Larva today.
Keywords: Julián Ríos; Contemporary Spanish Literature; Intellectual Networks; Larva operation; Literary Criticism; Modernity